Identifying and Prioritizing Factors Affecting the Effectiveness of Staff Training Quality Using Fuzzy AHP Technique (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper aims to identify the factors affecting the effectiveness of staff training quality using the fuzzy AHP technique. Due to a lack of attention and proper identification of the dimensions that affect the effectiveness of staff training and operating in a complex, competitive environment, universities often fail despite the high costs they spend on staff training. Therefore, research criteria have been extracted using library studies. The effect of their change on dependent variables was measured as independent variables, which are the same factors affecting the effectiveness of staff training quality. The research questionnaire was distributed among ten experts and administrators of Islamic Azad University, Neishabour Branch. In the present study, the experts and managers of the Islamic Azad University of Neishabour and an example of a group of 10 people in charge of specialized units in departments are the statistical populations. The research factors were analyzed using the multicriteria decision-making method and Excel and Expert Choice software fuzzy system